Activation of the Nrf2 signaling pathway and neuroprotection of nigral dopaminergic neurons by a novel synthetic compound KMS99220. (January 2018) - Lee, Ji Ae; Son, Hyo Jin; Choi, Ji Won; Kim, Jinwoo; Han, Se Hee; Shin, Nari; Kim, Ji Hyun; Kim, Soo Jeong; Heo, Jun Young; Kim, Dong Jin; Park, Ki Duk; Hwang, Onyou
Abstract: The transcription factor Nrf2 is known to induce gene expression of antioxidant enzymes and proteasome subunits. Because both oxidative stress and protein aggregation have damaging effects on neurons, activation of the Nrf2 signaling should be beneficial against neurodegeneration. In this study, we report a novel synthetic morpholine-containing chalcone KMS99220 that confers neuroprotection. It showed high binding affinity to the Nrf2 inhibitory protein Keap-1 and increased nuclear translocation of Nrf2 and gene expression of the antioxidant enzymes heme oxygenase-1, NAD(P)H:quinone oxidoreductase-1, and the catalytic and modifier subunits of glutamate-cysteine ligase in dopaminergic CATH.a cells. KMS99220 also increased expression of the proteasome subunits PSMB5, PSMB7, PSMB8 and PSMA1, and the respective chymotrypsin and trypsin-like proteasomal enzyme activities, and reduced α-synuclein aggregate in GFP-α-syn A53T-overexpressing cells. KMS99220 exhibited a favorable pharmacokinetic profile with excellent bioavailability and metabolic stability, did not interfere with activities of the cytochrome p450 isotypes, and showed no apparent in vivo toxicity when administered up to 2000 mg/kg. In 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine-treated mice, oral administration of KMS99220 prevented degeneration of the nigral dopaminergic neurons, induced the Nrf2 target genes, and effectively prevented the associated motor deficits. These results suggest KMS99220 as a potential candidate for therapy against Parkinson's disease. Highlights: We synthesized a novel compound KMS99220 that activates the Nrf2 signaling pathway. KMS99220 elevates Nrf2-dependent gene expression of HO-1, NQO1 and GCLM/GCLC. It raises expression and activities of proteases and lowers α-synuclein aggregation. It prevents nigral dopaminergic neurodegeneration and motor deficits in MPTP mice. It exhibits favorable pharmacokinetics, bioavailability and metabolic stability.